Elections and the Politics of Pork in the U.S. Senate1. (22nd June 2012) - Crespin, Michael H.; Finocchiaro, Charles J.
<x xml:space="preserve">Abstract</x> Objectives We examine the connection between pork‐barrel projects and the election returns of members of the U.S. Congress. While previous researchers have uncovered little evidence of a direct link, we refine the perspective that pork has electoral implications by advancing the argument that its effects differ across geographic and partisan contexts. Methods Our empirical analysis focuses on the Senate—which has largely escaped attention—and utilizes a measure of pork that includes only those projects inserted by legislators as line items in appropriation bills from 1996 to 2004. Results We find a direct relationship between pork and electoral performance, albeit one that is conditioned upon ideological congruence, constituency size, and the political ideology of the legislator. Conclusions Electoral payoffs for pork‐barreling accrue to some but not all senators. Moreover, our findings demonstrate the pragmatic rationale for conservative opposition to earmarks.